The Effectiveness of Psychological Well-Being Psychoeducation on Career Anxiety in Vocational High School Students Based on Gender - Purnama Putra, Surya Jaya; Suroso, Suroso; Farid, Muhammad (International Journal of Research in Counseling, 2025)
Background. Career anxiety is a common psychological concern among vocational high school students who are preparing to transition into the workforce. This anxiety can be influenced by various factors, including self-doubt, fear of failure, and uncertainty about future employment opportunities. Psychological well-being plays a crucial role in how students cope with career-related stress. Therefore, psychoeducational interventions designed to enhance psychological well-being may be effective in reducing career anxiety, particularly when gender differences are taken into account. Purpose. This study aimed to examine the effectiveness of psychological well-being psychoeducation in reducing career anxiety among vocational high school students. It also explored whether the intervention had different levels of effectiveness based on gender. Method. The study employed a quasi-experimental pretest-posttest control group design. Participants consisted of 100 vocational high school students (50 males and 50 females) from two different schools. The intervention group received psychological well-being psychoeducation over six sessions, focusing on self-acceptance, autonomy, purpose in life, positive relationships, personal growth, and environmental mastery. The career anxiety levels of all participants were measured before and after the intervention using a standardized career anxiety scale. Data were analyzed using paired sample t-tests and two-way ANOVA. Results. The results showed a significant reduction in career anxiety scores in the intervention group compared to the control group. Furthermore, female students demonstrated a greater decrease in anxiety levels than male students, suggesting that gender moderates the impact of psychological well-being psychoeducation on career-related stress. Conclusion. Psychoeducation focused on psychological well-being is effective in reducing career anxiety among vocational high school students. Gender differences in the outcomes highlight the need for tailored approaches in career counseling programs. Educational institutions are encouraged to incorporate structured psychoeducational modules to support students’ emotional and career readines.